Unpacking the “O” in VRIO : The role of workflow interdependence in the loss and replacement of strategic human capital - Kim, Jongsoo; Makadok, Richard (Strategic Management Journal, 2023)
Research Summary : An underresearched and undertheorized factor in the resource‐based view's VRIO acronym is the “O”: organizational deployment. Exploiting a rule change that exogenously shifted the workflow interdependence of NBA basketball teams, we examine how the benefit provided by a resource depends upon the way it is deployed in an organization's workflow. We also examine how workflow interdependence influences the relative effectiveness of two capabilities for obtaining resources—external acquisition versus internal development. We find that losing star players is more damaging under conditions of greater pooled interdependence and that external acquisition capabilities are more effective for mitigating this damage. Conversely, we find that losing non‐star players is more damaging under conditions of greater reciprocal interdependence and that internal development capabilities are more effective for mitigating this damage. Managerial Summary : Different organizations arrange their workflows in different ways. Some organizations use more individual‐focused workflows, where the performance of each employee is relatively independent of the performance of coworkers, while others use more team‐focused workflows, where the performance of each employee depends critically on the performance of coworkers. Does an organization's way of arranging its workflow affect the amount of damage done when a key employee quits? Does the answer depend upon whether the departing employee is a star performer? Does it depend upon the organization's capability for recruiting high‐potential replacements from other organizations, or its capability for improving the performance of its existing employees? By analyzing data from NBA basketball teams, we find that the loss of a star player is more damaging when teams use a more individual‐focused workflow, but that capability for recruiting high‐potential players mitigates this damage. Conversely, we also find that the loss of a non‑star player is more damaging when teams use a more team‐focused workflow, but that capability for improving performance of a team's existing players mitigates this damage. So, our results suggest that organizations should develop capabilities that fit their workflow and their relative risk of losing star employees versus non‑stars.